2005
DOI: 10.1093/molbev/msi145
|View full text |Cite
|
Sign up to set email alerts
|

Time Dependency of Molecular Rate Estimates and Systematic Overestimation of Recent Divergence Times

Abstract: Studies of molecular evolutionary rates have yielded a wide range of rate estimates for various genes and taxa. Recent studies based on population-level and pedigree data have produced remarkably high estimates of mutation rate, which strongly contrast with substitution rates inferred in phylogenetic (species-level) studies. Using Bayesian analysis with a relaxed-clock model, we estimated rates for three groups of mitochondrial data: avian protein-coding genes, primate protein-coding genes, and primate d-loop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

64
943
7
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 966 publications
(1,019 citation statements)
references
References 43 publications
64
943
7
5
Order By: Relevance
“…It is known that many factors may influence viral substitution rates and their variation over time [72]. Various methodological biases probably influence the calculation of both short-and long-term rates and therefore could explain the large difference between these rates [3,5,73,74], which has also been observed in cellular organisms [75]. Specifically, it has been recently shown that pervasive purifying selection could be one of the major obstacles in accurately estimating the ancient age of recent pathogens [76], and the development of substitution models accounting for this phenomenon are beginning to yield more realistic results [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that many factors may influence viral substitution rates and their variation over time [72]. Various methodological biases probably influence the calculation of both short-and long-term rates and therefore could explain the large difference between these rates [3,5,73,74], which has also been observed in cellular organisms [75]. Specifically, it has been recently shown that pervasive purifying selection could be one of the major obstacles in accurately estimating the ancient age of recent pathogens [76], and the development of substitution models accounting for this phenomenon are beginning to yield more realistic results [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…Yet such discrepancies may indicate that rate heterogeneity and other features of the control region in humans rapidly generate homoplasy that complicates estimates of rates. Recent studies on time dependence of molecular rates indicate that substitution rates are generally underestimated in a phylogenetic comparison of old divergences, and that comparing more recently diverged taxa provides better estimates of instantaneous substitution rates (Ho et al 2005;Ho and Larson 2006;Burridge et al 2008). For whales, fossil dates for divergences are old because the fossil record of modern species is poor.…”
Section: Estimating Control Region Rate Using Cytochrome B Datamentioning
confidence: 99%
“…Using this approach, a decay in nucleotide substitution rates with time has been identified across the population-species transition [3,4]. However, both the magnitude and the timing of any decay are hotly contested [5 -7], with particular focus on errors that may arise from the use of ancient DNA sequences to infer molecular rates [8 -10].…”
Section: Introductionmentioning
confidence: 99%